Experimental Verification of Failure Criterion Based on Specific Strain Work - Żuchowski, R.; Korusiewicz, L. (Engineering Transactions, 1984)
The difference between values of specific strain work needed for rupturing (at room temperature) the virgin specimen and that previously subjected to a loading process until the specified cycle number is reached had been proposed earlier by one of the authors' as a material damage measure and failure criterion. These assumptions were verified during the investigation reported in this paper. The analysis of results obtained shows that the maximum of that difference is constant and independent of stress and temperature (for examined steels and process parameters applied); it can thus be accepted as a failure criterion.